Penentuan Karyawan Terbaik di Perusahaan Citra Bogor Menggunakan Metode TOPSIS - Galuh Krisna Dewanti; Ade Kurnia Solihin; Fauzan Natsir; Danang Mulyadipa Suratno (INTEKSIS, 2025)
Determining the best employee is an essential process in human resource management because it affects work motivation, productivity, and performance appraisal rewards. Manual evaluation often leads to subjectivity and inaccuracies in decision-making. To address this issue, this study develops a web-based Decision Support System (DSS) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to determine the best employee at Citra Company, Bogor. The evaluation criteria consist of four aspects: performance (C1), experience (C2), education (C3), and attendance (C4), with respective weights of 0.30, 0.25, 0.25, and 0.20. The system was designed using Unified Modeling Language (UML) and implemented as a web-based application with an interactive user interface.The results of the TOPSIS calculation indicate that employee A1 (Budi) achieved the highest preference score of 0.7273, thus being selected as the best employee. The ranking results are visualized through a bar chart, allowing users to interpret the decision outcomes quickly and objectively. Based on the testing results, the developed system successfully reduces subjectivity, accelerates the evaluation process, and provides outcomes consistent with actual performance conditions. Therefore, the implementation of the TOPSIS method is proven to be effective in supporting decision-making for determining the best employee in an objective and transparent manner.